Pengaruh Tingkat Pendidikan, Literasi Keuangan Dan Inklusi Keuangan Terhadap Perilaku Keuangan UMKM Kuliner Kota PADANG - Awliya Rahmat; Reno Fithri Meuthia; Eka Rosalina (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of education level, financial literacy, and financial inclusion on the financial behavior of culinary MSMEs in Nanggalo District, Padang City. This study used quantitative methods with primary data obtained through questionnaires distributed to 120 MSMEs as the research sample. The sampling technique used was convenience sampling. Data analysis was conducted using multiple linear regression analysis using SPSS. The results of the study indicate that education level has a negative influence on financial behavior, financial literacy has a positive influence on financial behavior, and financial inclusion has a negative influence on the financial behavior of MSMEs. This suggests that the higher the level of education, understanding of financial literacy, and access to formal financial services, the better the financial behavior of MSMEs in managing their businesses.